TRANSFORMASI DIGITAL DALAM PELAYANAN PUBLIK: IMPLIKASI DAN TANTANGAN HUKUM ADMINISTRASI NEGARA - Loso Judijanto; Al-Amin (ADMIN: Jurnal Administrasi Negara, 2025)
Digital transformation in public services offers increased efficiency, transparency, and accessibility, but also presents significant challenges in the context of State Administrative Law. These challenges include regulatory adjustments to new technologies, uneven digital infrastructure, cybersecurity issues, and changes in organisational culture in government agencies. In addition, the issue of interoperability between government agency systems and the financing required for digital technologies is also a major concern. The protection of personal data and upholding the principle of good governance are important aspects that must be maintained in the digital administration process. With effective collaboration between the government, the private sector, and the community, it is hoped that these challenges can be overcome, so that digital transformation can provide optimal benefits for public services.